The impact of solvent relative permittivity on the dimerisation of organic molecules well below their solubility limits: examples from brewed coffee and beyond. Issue 3 (31st January 2017) - Bradley, Ellen S.; Hendon, Christopher H.
Abstract : Changes in solvent relative permittivity do not greatly affect the dimerisation energies of compounds contained therein. Abstract : The formation of aqueous intermolecular dimers is governed by both the nature and strength of the intermolecular interactions and the entropy of dissolution. The former interaction energies are determined by the polarity of the solvent and the functionality of the solute. Using quantum chemical methods, we probe the energetics of dimer formation of representative compounds found in coffee well below their solubility limits. We find that with the exclusion of entropy, the dimer formation is thermodynamically unfavorable with negligible dependence on the dielectric medium.